(untitled) (Medico Legal Update, 2020)
A role of health officer to prevent stunting rate was very significant, especially on first 1000 days of life. The role of health officer within program of stunting prevention was divided into three parts: basic role, the role on specific nutritional intervention, since the role on nutritional intervention was regarded as sensitive aspect. This research aimed to analyze the effect of implementation from health officer to the program of stunting prevention on the first 1000 days of life, This research was categorized into quantitative research which exerted case control approach, while the data analysis employed bivariate data analysis with logistic regression analysis test. The research sample was taken through cluster random sampling in approximately 275 respondents. The result of data analysis showed the effect of health officer basic role to the stunting prevention. Moreover, the analysis result from those three variables indicated p value ? 0,05, it referred that this variable did not get to be confounding factor in this research and it referred that the significant effect was not existed between health officer role and stunting prevention program on the first 1000 days of life in Indonesia. This result demonstrated that the variable of specific nutrition intervention became the most effective aspect to the program of stunting prevention on the first 1000 day of life, it produced OR value 0.703 (95% CI: 0.504-0.981). Therefore, the good specific nutrition intervention has the biggest chance as much as 0.703 times in order to prevent stunting rather than the poor specific nutrition intervention.